Environmental migration of Sub-Saharan countries - Potînga, Adriana; Votoupalová, Markéta; Strachová, Nikola; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2021)
Environmental and climate change has been discussed and debated in the economy, social sciences, migration theories, and other areas of studies. Climate change is a phenomenon that affects people beyond state borders. And although we often talk about the consequences of climate change that will take place in the future, people around the world are already confronted with difficulties caused by climate change as such are the areas of the sub-Saharan region which reflect in this work. Climate change leads to still poorly but already existing migrant patterns. The reason for this can be various extreme weather phenomena - for example, flooding or droughts that deprive residents of susceptible to regions access to vital resources. Still, adequate assessment of international migration flows is highly complicated. Often it is difficult to determine why people go. Some are forced, and others prefer to migrate. This paper offers an analysis and tries to demonstrate whether there is a link between migration and environmental influences in the sub-Saharan region. Also, it will analyse theories of which the cause of migration is besides climate. The paper is organized around two questions: Is there an agreement between scholars about the link between migration and environmental changes? Is the environment a fundamental cause of international migration in the region? As the main findings, I could point out that migration has different causes, not the only environment. As we will see through the paper, those causes are political reasons such as conflicts, economic as low wages and low standards of living, and environmental causes. But we can see that even if there are environmental problems, they aren’t triggered for migration alone but connected with other factors mentioned previously. In sub-Saharan Africa, this is also the case of movement. People are relocated because of climate changes, usually nearly, not to other countries in sudden events.
Still, if the changes are slow going, migration is because of a mix of factors.
Vedoucí práce: Markéta Votoupalová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor dipl. práce]; diplomové práce; master's theses